The GATA-Type Transcription Factor Csm1 Regulates Conidiation and Secondary Metabolism in Fusarium fujikuroi - Niehaus, Eva-Maria; Schumacher, Julia; Burkhardt, Immo; Rabe, Patrick; Münsterkötter, Martin; Güldener, Ulrich; Sieber, Christian M. K.; Dickschat, Jeroen S.; Tudzynski, Bettina (Frontiers in Microbiology, 2017)
GATA-type transcription factors (TFs) such as the nitrogen regulators AreA and AreB, or the light-responsive TFs WC-1 and WC-2, play global roles in fungal growth and development. The conserved GATA TF NsdD is known as an activator of sexual development and key repressor of conidiation in Aspergillus nidulans, and as light-regulated repressor of macroconidia formation in Botrytis cinerea. In the present study, we functionally characterized the NsdD ortholog in Fusarium fujikuroi, named Csm1. Deletion of this gene resulted in elevated microconidia formation in the wild type (WT) and restoration of conidiation in the non-sporulating velvet mutant ∆vel1 demonstrating that Csm1 also plays a role as repressor of conidiation in F. fujikuroi. Furthermore, biosynthesis of the two PKS-derived red pigments, bikaverin and fusarubins, is de-regulated under otherwise repressing conditions. Cross-species complementation of the ∆csm1 mutant with the B. cinerea ortholog LTF1 led to full restoration of WT-like growth, conidiation and pigment formation. In contrast, the F. fujikuroi CSM1 rescued only the defects in growth, the tolerance to H2O2 and virulence, but did not restore the light-dependent differentiation when expressed in the B. cinerea ∆ltf1 mutant. Microarray analysis comparing the expression profiles of the F. fujikuroi WT and the ∆csm1 mutant under different nitrogen conditions revealed a strong impact of this GATA TF on 19 of the 47 gene clusters in the genome of F. fujikuroi. One of the up-regulated silent gene clusters is the one containing the sesquiterpene cyclase-encoding key gene STC1. Heterologous expression of STC1 in Escherichia coli enabled us to identify the product as the volatile bioactive compound (–)-germacrene D.